2016
DOI: 10.1055/s-0036-1583300
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Rolando Fractures by Open Reduction and Internal Fixation using Mini T-Plate and Screws

Abstract: Introduction?Rolando fractures being intra-articular fractures of the most mobile joint of the thumb, assume significance because any residual incongruity of the articular surface may result in loss of motion as well as secondary osteoarthritis and hence serious disability. This fracture continues to pose difficulties to the treating surgeons and although several treatment options have been described for these fractures, there are no definite guidelines. Methods?The present study describes the results of open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, long-term soft tissue problems, particularly in dorsal plate applications, may arise. Mumtaz et al[ 18 ] found that four out of nine patients who were treated with a dorsal plate experienced local tenderness and pain, which resulted in the early removal of the plate and screws. The reduction of the volar part in Bennett's fractures may be difficult to identify and evaluate with the dorsal approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term soft tissue problems, particularly in dorsal plate applications, may arise. Mumtaz et al[ 18 ] found that four out of nine patients who were treated with a dorsal plate experienced local tenderness and pain, which resulted in the early removal of the plate and screws. The reduction of the volar part in Bennett's fractures may be difficult to identify and evaluate with the dorsal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Development of soft tissue problems, devascularization of fracture fragments, and collateral ligament and tendon injuries are more common in this method. In a study by Mumtaz et al [ 14 ], the implant was required to be removed in four of nine patients, who underwent open reduction and plate osteosynthesis, due to local tenderness and pain, and soft tissue problem and superficial infection were reported in two patients. Closed reduction and external fixator and pinning is presented as a much safer method for fractures of this region in terms of both joint restoration and early mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…However, treating a Rolando fracture can be challenging due to the inherent nature of instability and comminuted patterns. There is also the risk of complications such as loss of reduction, joint incongruity, or the development of osteoarthritis [54,59].…”
Section: Treatmentmentioning
confidence: 99%